Dentistry Students' Knowledge of Pediatric Patients Who Suffered Violence: A Systematic Review - Isadora Augusta da Silveira; Larissa Moreira Pinto; Luciana Domingues Conceição; Marina Sousa Avezedo; Rafael Guerra Lund (Association of Support to Oral Health Research (APESB), 2024)
Objective: To review the literature unprecedentedly to identify the dentistry students' knowledge of pediatric patients who suffered violence. Material and Methods: A systematic review was conducted using PubMed, Web of Science, LILACS, SciELO, Google Scholar, and OpenGrey electronic databases up to November 2021. The "Grey Literature" was verified through Google Scholar and Open Grey searches to avoid any selection bias. There was no restriction on the date of publication or language. Results: The systematic search yielded 2.756 studies in the first selection phase, but only twenty-two articles were included. All selected articles were published between 1998 and 2021 and used a questionnaire to evaluate the dentistry students' knowledge regarding child maltreatment cases. Brazil was the country that had the most studies included (10 articles). Despite the majority of the students presenting insufficient knowledge about child maltreatment, evidence from this research showed that every form of approach by professionals toward child maltreatment should be considered important. Conclusion: Therefore, there are deficiencies regarding the teaching-learning methodology, reinforcing the need for improvements in Dentistry undergraduate curricula.